The opening and closing sequences of Malaysian vlogs / Goh Vern Jan - Goh, Vern Jan (2014)
This paper looks at the opening and closing strategies of Malaysian vlogs. Aside from these strategies, the non-verbal communication of the vloggers are analysed as well. This paper also investigates the vlog viewers’ perception regarding the importance of openings and closings in vlogs. Frobenius’s (2011) taxonomy of opening strategies and Coronel-Molina’s (1998) closing strategies are used as the framework for analyzing the data. Qualitative research is used to examine the data, which consists of 30 monologue vlogs from YouTube. The openings and closings of the vloggers are analysed using Conversation Analysis (CA). This approach facilitates the transcription of their monologues and the study of the structure of the openings and closings. Meanwhile, 40 viewers are interviewed online to obtain their opinions of opening and closing sequences. Content analysis is employed to inspect the responses of the viewers as it allows the extraction of lexical items that reflect their opinions. Apart from Frobenius’s (2011) strategies, the Malaysian vloggers used four other types of opening strategies: small talk, pleasantries, request for feedback and apologies. They also used three other closing strategies, which are not found in Coronel-Molina’s (1998) data: apologies, request for feedback and self-identification. Such findings suggest that opening and closing strategies are influenced by social and cultural expectations. Furthermore, the interview results show that Malaysian viewers generally consider opening and closing sequences important as they believe these sequences serve necessary functions. Keywords: vlog, monologue, opening sequence, closing sequence, Malaysian vloggers, viewer perception